2010
DOI: 10.1002/rcm.4641
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and analytical development of the CIME cocktail for drug fate assessment in humans

Abstract: Phenotyping based on drug metabolism activity appears to be informative regarding mechanism-based interactions during drug development. We report here the first steps of the development of the innovative CIME cocktail. This cocktail is designed not only for the major cytochrome P450, with caffeine, amodiaquine, tolbutamide, omeprazole, dextromethorphan and midazolam as substrates of CYP1A2, CYP2C8, CYP2C9, CYP2C19, CYP2D6 and CYP3A, respectively, but also phase II enzymes UGT 1A1/6/9 with acetaminophen, P-gp a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Amodiaquine was selected for the first version of the CIME combination (Videau et al 2010;Prot et al 2011). However, the ethics committee was surprised by this use since several cases of severe toxicity have been reported with amodiaquine (Guevart and Aguemon 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Amodiaquine was selected for the first version of the CIME combination (Videau et al 2010;Prot et al 2011). However, the ethics committee was surprised by this use since several cases of severe toxicity have been reported with amodiaquine (Guevart and Aguemon 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The CIME combination was designed to limit the risk of potential interaction between probes by: (a) selection of well-known substrates with no or few predictable interactions based on the Metabolism and Transport Drug Interaction Database (http://www.druginteractioninfo.org/) and the literature and (b) choice of low doses [previously discussed in (Videau et al 2010)], but not microdoses minimizing pharmacokinetic linearity issues. The probe doses are generally below the therapeutic range, but are used only for metabolic purposes and allow the production of metabolites for all the CYPs studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scott et al reported an LC-MS/MS method for six probe drugs and their metabolites in both plasma and urine [24], Yin et al validated a similar approach for five drugs and their metabolites [25], Zhang et al developed an assay for four parent probe drugs in human plasma [26], and Videau et al presented a UPLC-MS/MS assay for ten probe drugs and ten metabolites in human plasma [27]. The overarching goal in each of these studies was the same as for the current work — to accelerate and simplify the processing and analysis of samples for probe drug studies, such that the efficiency of subject treatment and sampling is matched by the efficiency of the analytical process.…”
Section: Discussionmentioning
confidence: 99%